Correlation between Body Mass Index and Disability in Patient with Chronic Low Back Pain - Tiang Soon Teck; Tertianto Prabowo; Nani Kurniani (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Low back pain is discomfort presented below the margin of the 12th thoracic rib and above the inferior gluteal fold with or without leg pain. It is also a major cause of disability. Several risk factors have been identified for contributing low back pain. It is important to determine whether body mass index (BMI) can affect the disability in patients with chronic low back pain. Oswestry disability index (ODI) questionnaire has been used to measure the severity of disability. Thus, the focus of study was to determine correlation between BMI and disability in patients with chronic low back pain. Methods: Sixty two patients aged 18 years old or more who were clinically diagnosed as having low back pain at least 3 months participated in this study in the period of October to November 2015 in the Department of Physical Medicine and Rehabilitation of Dr. Hasan Sadikin General Hospital Bandung. Total sampling method was used. Gender, age, weight, height, BMI and disability were recorded using ODI questionnaire. This analytical study was cross sectional study and the ordinal variable was analyzed using linear regression analysis.Results: Females had higher proportion (77). Chronic low back pain patients were equally distributed on normal weight and overweight categories. Patient with chronic low back pain had higher chances of developing moderate disability. There were positive correlation between BMI and disability. Nevertheless, there was no statistically analysis difference between model 1 and 2.Conclusions: The BMI affects the disability in patients with chronic low back pain. [AMJ.2016;3(4):624–8] DOI: 10.15850/amj.v3n4.949